2006
DOI: 10.2215/cjn.02021205
|View full text |Cite
|
Sign up to set email alerts
|

Histologic versus Molecular Diagnosis of BK Polyomavirus–Associated Nephropathy

Abstract: Although discovered in 1970 the BK virus infections had no significant clinical impact until the emergence of BK virusassociated allograft nephropathy (BKPVAN). Escalating clinical challenges required better diagnostic tools and delineation of uniform criteria for diagnosis. In recent years, the widespread use of real-time PCR for measuring viral loads has confirmed that BK viruria and viremia are consistently identified before the development of overt nephritis. The identification of this viruria-viremia-neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 38 publications
(96 reference statements)
0
55
0
6
Order By: Relevance
“…Moreover, LT is conveniently detectable in the nuclei of renal tubular epithelial cells with activated BKV replication and precedes the late gene expression of agnoprotein or the capsid protein VP1 (24,34,44,45). In fact, positive immunohistochemistry detecting intranuclear LT has been established as the standard confirmatory assay for the diagnosis of PVAN in renal allograft biopsies (5,18,28,37,40). The lower-antibody response despite its relative abundance suggests differences in immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LT is conveniently detectable in the nuclei of renal tubular epithelial cells with activated BKV replication and precedes the late gene expression of agnoprotein or the capsid protein VP1 (24,34,44,45). In fact, positive immunohistochemistry detecting intranuclear LT has been established as the standard confirmatory assay for the diagnosis of PVAN in renal allograft biopsies (5,18,28,37,40). The lower-antibody response despite its relative abundance suggests differences in immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…There are other limitations of this study. First, given the evolution of BKVAN screening and histologic classification over time, not every patient had quantitative PCR monitoring, biopsy scoring, or prior screening for BKVAN; thus, these characteristics were not included in this analysis despite their proven value (8,9,19). We attempted to account for these deficiencies by examining BKVAN outcomes segregated into separate eras and found that there was no difference in outcomes between eras on univariate or multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the biopsy findings at diagnosis are proposed to be a predictive tool for assessing prognosis (18,19), quantitative assessments of viral load at diagnosis have generally not been predictive of outcomes. To date, there has not been an assessment of clinical risk factors for disease progression or a comparison of immunosuppression withdrawal strategies.…”
mentioning
confidence: 99%
“…Borderline inflammatory changes were considered to be an acute rejection. Polyoma-associated nephropathy (PVAN) was diagnosed by the presence of BK virus DNA in the allograft biopsy by in situ hybridization (15,16).…”
Section: Posttransplant Monitoringmentioning
confidence: 99%